2018
DOI: 10.3390/lubricants6010019
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipid Vesicles in Media for Tribological Studies against Live Cartilage

Abstract: Introduction Pre-clinical testing of hemiarthroplasty devices requires that the tribological conditions present in vivo with live cartilage be closely duplicated. A current limitation in the tribological testing of live cartilage involves the use of cell-culture media as lubricant. Study Aim to develop and test a new hyaluronan-phospholipid based medium (HA–phospholipid medium) that combines the rheological and frictional properties of synovial fluid with the nourishing properties of culture media to keep ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 48 publications
(55 reference statements)
2
15
0
Order By: Relevance
“…In the hydration lubrication paradigm surfaces interact via fluid but tenaciously attached hydration layers exposed by their boundary layers at the slip plane, resulting in low friction as surfaces slide past each other [ 12 , 58 ]. Previous studies [ 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 56 , 59 , 60 , 61 , 62 , 63 , 64 ] showed that HA interacts with PC lipids when they are dispersed in aqueous solution or when the phospholipids are incubated with pre-adsorbed HA on a surface, due to charge-dipole interactions between the negatively charged HA and the exposed zwitterionic phosphocholine headgroups. Thus one would expect that HA would adsorb at a phospholipid-bilayer/water interface.…”
Section: Discussionmentioning
confidence: 99%
“…In the hydration lubrication paradigm surfaces interact via fluid but tenaciously attached hydration layers exposed by their boundary layers at the slip plane, resulting in low friction as surfaces slide past each other [ 12 , 58 ]. Previous studies [ 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 56 , 59 , 60 , 61 , 62 , 63 , 64 ] showed that HA interacts with PC lipids when they are dispersed in aqueous solution or when the phospholipids are incubated with pre-adsorbed HA on a surface, due to charge-dipole interactions between the negatively charged HA and the exposed zwitterionic phosphocholine headgroups. Thus one would expect that HA would adsorb at a phospholipid-bilayer/water interface.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, functional metal oxide nanosystems have been developed to transport agents of natural [ 182 ] or synthetic antioxidants [ 178 ]. The most efficient nanosystems were made up of soft nanoparticles, such as polymeric micelles [ 183 ], nanoemulsions [ 184 ], and lipid vesicles [ 185 ].…”
Section: The Effects Of Antioxidants In Koamentioning
confidence: 99%
“…With regard to the fluid viscosity, any addition of HA is certainly associated with an increase in fluid viscosity. Based on published viscosity measurements on simulated synovial fluids [20, 32], the viscosity of DPBS + HA is approximately 10 times higher than the viscosity of DPBS. The mobility of ions ‘ u ’ is inversely proportional to the fluid viscosity (4) [22]: u=(|z|·e)/6·π·η·r where ‘ z ’ is the magnitude of the ion's charge, ‘ e ’ the electronic charge, ‘ η ’ the fluid viscosity, and ‘ r ’ the ion's radius.…”
Section: Discussionmentioning
confidence: 99%